Cardiovascular Diseases Increase Cancer Mortality in Adults: NHANES‐Continuous Study - Omar M. Makram; Tochukwu Okwuosa; Daniel Addison; Jorge Cortes; Susan Dent; Malcolm Bevel; Sarju Ganatra; Sadeer Al‐Kindi; Catherine C Hedrick; Neal L Weintraub; Xiaoling Wang; Avirup Guha (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Both cancer and cardiovascular disease (CVD) are the leading causes of death worldwide. Although our previous study detected a relationship between CVD and cancer incidence, limited evidence is available regarding the relationship between CVD, cardiovascular risk factors, and cancer mortality. Methods and Results A prospective cohort study using data from the continuous NHANES (National Health and Nutrition Examination Survey, 1999–2016) merged with Medicare and National Death Index mortality data, through December 31, 2018. We included individuals with no history of cancer at baseline. The primary exposure was CVD at baseline. We also conducted a comprehensive risk factor analysis as secondary exposure. The main outcome was cancer mortality data collected from Medicare and National Death Index. We included 44 591 adult individuals representing 1 738 423 317 individuals (52% female, 67% non‐Hispanic White, and 9% Hispanic). Competing risk modeling showed a significantly higher risk of cancer mortality in individuals with CVD (adjusted hazard ratio [aHR], 1.37 [95% CI 1.07–1.76], P=0.01) after adjusting for age, sex, and race and ethnicity. Notably, cancer mortality increased with aging (aHR, 1.08 [95% CI 1.05–1.11], P<0.0001), current smoking status (aHR, 6.78 [95% CI, 3.43–13.42], P<0.0001), and obesity (aHR, 2.32 [95% CI, 1.13–4.79], P=0.02). Finally, a significant interaction (P=0.034) was found where those with CVD and obesity showed higher cancer mortality than those with normal body mass index (aHR, 1.73 [95% CI, 1.03–2.91], P=0.04). Conclusions Our study highlights the close relationship between cardiovascular health and cancer mortality. Our findings suggest that obesity may play a significant role in cancer mortality among individuals with CVD. These findings emphasize the need for a more proactive approach in managing the shared risk factors for CVD and cancer.